The Value of PIC Cystography in Detecting De Novo and Residual Vesicoureteral Reflux after Dextranomer/Hyaluronic Acid Copolymer Injection - B. W. Palmer; M. Hemphill; K. Wettengel; B. P. Kropp; D. Frimberger (International Journal of Nephrology)
The endoscopic injection of Dx/HA in the management of vesicoureteral reflux (VUR) has become an accepted alternative to open surgery. In the current study we evaluated the value of cystography to detect de novo contralateral VUR in unilateral cases of VUR at the time of Dx/HA injection and correlated the findings of immediate post-Dx/HA injection cystography during the same anesthesia to 2-month postoperative VCUG to evaluate its ability to predict successful surgical outcomes. The current study aimed to evaluate whether an intraoperatively performed cystogram could replace postoperative studies. But a negative intraoperative cystogram correlates with the postoperative study in only 80%. Considering the 75–80% success rate of Dx/HA implantation, the addition of intraoperative cystograms cannot replace postoperative studies. In patients treated with unilateral VUR, PIC cystography can detect occult VUR and prevent postoperative contralateral new onset of VUR.